Red blood cell distribution width is associated with myocardial injury in non-ST-elevation acute coronary syndrome (Clinics, 2015)
OBJECTIVES: The red blood cell distribution width has been associated with an increased risk of cardiovascular events. In the present study, we assessed the relationship between red cell distribution width values and cardiac troponin I levels in patients admitted with non-ST-elevation acute coronary syndrome. METHODS: We analyzed blood parameters in 251 adult patients who were consecutively admitted to the intensive coronary care unit with non-ST-elevation acute coronary syndrome over a 1-year period. For all patients, a baseline blood sample was collected for routine hematological testing. Cardiac troponin I was measured at baseline and after 6 h. The patients were diagnosed with non-ST-elevation myocardial infarction or unstable angina based on the elevation of cardiac troponin I levels. RESULTS: The red cell distribution width was higher in the group with non-ST-elevation myocardial infarction compared with the patient group with unstable angina (14.6±1.0 vs 13.06±1.7, respectively; p = 0.006). Coronary thrombus was detected more frequently in the group of patients with non-ST-elevation myocardial infarction than in the patients with unstable angina (72% vs 51%, respectively; p = 0.007). Using receiver operating characteristic curve analysis for the prediction of non-ST-elevation myocardial infarction based on the red cell distribution width, the area under the curve was 0.649 (95% confidence interval: 0.546-0.753; p = 0.006), suggesting a modest model for the prediction of non-ST-elevation myocardial infarction using the red cell distribution width. At a cut-off value of 14%, the sensitivity and specificity of the red cell distribution width were 73% and 59%, respectively. Additionally, the red cell distribution width was positively correlated with cardiac troponin I (r = 0.19; p = 0.006). CONCLUSION: A greater baseline red cell distribution width value was associated with myocardial injury and elevated cardiac troponin I levels in non-ST-elevation acute coronary syndrome. Therefore, the red cell distribution width could be considered for risk stratification of acute coronary syndrome patients admitted to emergency departments.